Influence of crumb rubber particle size and SBS structure on properties of CR/SBS composite modified asphalt. (28th February 2020) - Qian, Chengduo; Fan, Weiyu; Yang, Guoming; Han, Ling; Xing, Baodong; Lv, Xiaobo
Graphical abstract: Highlights: Impact of CR particle size as well as SBS structure on properties was studied. Larger CR particles and lower styrene content help rutting and fatigue resistance. Smaller CR particles and less styrene benefit low-temperature cracking resistance. Smaller CR particles and SBS with lower styrene content are more stable. The combination of CR and SBS copolymers has a synergistic effect on rheology. Abstract: The performance of asphalt can be improved using various additives, such as SBS (styrene-butadienestyrene) and crumbed rubber (CR). This paper investigated the influence of CR particle size and SBS structure on the properties of CR/SBS modified binders. CR/SBS composite modified asphalts were obtained by mixing asphalt, CR of various particle sizes, and SBS copolymers with various molecular structures, and were then subjected to conventional measurements, rheological characterization, and thermal storage tests. The results demonstrated that larger CR particles enhanced rutting and fatigue resistance but reduced low-temperature cracking resistance and storage stability. Modified asphalt containing 20 wt% styrene showed the best rheological properties, followed by those with 30 wt% and 40 wt% styrene. Meanwhile, SBS copolymers with lower styrene contents showed better thermal storage stability. Addition of larger CR particles and lower-styrene SBS copolymers increased rutting and fatigue resistance, while smaller CR particles and lower-styrene SBS copolymers benefited low-temperature cracking resistance and stability. The combination of CR and SBS copolymers has a synergistic effect on asphalt's rheological properties, thereby lowering the amounts of additives required and improving the cost-effectiveness of CR/SBS modified asphalt.